The role of multislice computed tomography (MSCT) in the direction of traumatic intra abdominal injury : our experience in Hospital Tengku Ampuan Afzan(HTAA), Kuantan, Pahang - Hassan, Radhiana; Abd. Aziz, Azian; Abdul Rashid, Mohd Amran; Sa'at@Yusof, Azlin (2010)
Introduction: Blunt abdominal trauma can cause multiple injuries and these injuries are often difficult to be accurately evaluated via clinical assessment. Currently, multislice computed tomography (MSCT) scan is the imaging modality of choice in assessing clinically stable patients with blunt abdominal trauma. This study assessed the role of MSCT in the detection of traumatic intra abdominal injury and correlates the findings with subsequent patient’s management. Methodology This is a retrospective study approved by our institutional review board. All cases of CT scan performed to rule out traumatic intra abdominal injury from January 2008 until December 2009 was traced from the registration book. CT scan images were retrieved and reviewed. Analysis of findings was done and organ injuries were graded according to AAST (American Association of Surgery and Trauma). Case notes and surgical findings were reviewed for correlation with CT findings. Results There were 151 cases included in this study. Positive scan were seen in 130 patients (86.1%). Liver, spleen and renal injuries were seen in 40.8%, 33.8% and 26.2% of cases respectively. Laparotomies were performed in 42 patients from 130 positive scans (32.3%) and in 3 patients who had negative scan. Out of 45 patients who had undergone laparotomies, 10 patients had significant surgically injuries that were missed on CT scan findings. The injuries were bowel perforation (n=4), serosal tear of bowel (n=1), mesenteric injuries (n=2), spleen injury (n=1), liver injury (n=1) and laceration of broad ligaments with oozing of blood from ovarian artery (n=1).